2020
DOI: 10.3390/ma13030807
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ultrasonic Bending Vibration Introduced by the L-shaped Ultrasonic Rod on Solidification Structure and Segregation of Large 2A14 Ingots

Abstract: In order to achieve long-term and stable ultrasonic treatment in the direct chill semi-continuous casting process, a new L-shaped ceramic ultrasonic wave guide rod is designed to introduce ultrasonic bending vibration into 2A14 aluminum alloy melt. The effect of ultrasonic bending vibration on the solidification structure and composition segregation of large 2A14 aluminum alloy ingots (ϕ 830 mm × 6000 mm) in the process of semi-continuous casting were studied by means of a direct reading spectrometer, scanning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Coarse and inhomogeneous microstructures always occur during conventional direct chill casting (DCC) of billets, an issue that usually worsens as the scale of the billet and range of solidification increases [ 1 , 2 , 3 , 4 ]. Deformation processes, such as rolling and forging, can refine a microstructure, but cannot significantly improve its inhomogeneity [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Coarse and inhomogeneous microstructures always occur during conventional direct chill casting (DCC) of billets, an issue that usually worsens as the scale of the billet and range of solidification increases [ 1 , 2 , 3 , 4 ]. Deformation processes, such as rolling and forging, can refine a microstructure, but cannot significantly improve its inhomogeneity [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, our research group has developed a new type of L-shaped ultrasonic rod which uses a nano ceramic radiator to avoid the ultrasonic transducer being directly affected by high-temperature heat radiation and resist the erosion of metal melt, which can meet the requirements of long-term continuous work and is conducive to industrial application. Shi et al [28] applied the L-shaped ultrasonic device to the solidification process of a large 2A14 aluminum alloy ingot (ϕ830 mm × 6000 mm). The study showed that it can significantly refine the grains of the large ingot, effectively decrease the degree of solute segregation, and improve its mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Streaming would disperse the aggregate in the melt and fuse dendrites to produce small particles, which can act as the core of heterogeneous nucleation. Under the synergistic effect of cavitation and streaming, the nucleation rate of alloy was improved during cooling and solidification process [ 14 ]. After intense streaming, the segregation would be destroyed and reducing the grain boundary segregation and the microhardness of samples would also change because of ultrasonic treatment [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%